The Spatial Development of the Rural Settlement of East Prussia: Kaliningrad Region - Levchenkov, Andrey V.; Gumenyuk, Ivan S. (International Journal of Economics and Financial Issues, 2015)
The present system of displacement of the Kaliningrad region's population results from a complicated historical process, during which the socio-economic, geopolitical and cultural conditions were repeatedly changed in which it was established. An analysis of the changes taking place at that time and now provides the basis for the preparation of forecasts of further transformation of the region's spatial environment, one of the most important tasks for specialists of the contemporary geographical science. In the publication, the authors examine the key historical stages of the creation of the modern system of displacement of the region's population and identify the key economic, political and social factors that had an impact on the process at various historical stages of development of East Prussia until 1945 and the contemporary Kaliningrad region. The so-called Nizhnenemanskaya lowland area was chosen as a local example of the transformation processes of the modern part of the Slavsk municipal district (north of the Kaliningrad region). The research results were obtained in the analysis of the cartographic material on the status of the area related to the study of three time stages, 1834-1960, 1914-1939 and 2010-2012. It became possible to compare the cartographic material featuring such a broad time horizon due to the project of the Russian Geographical Society ‘Post-War Changes in the Kaliningrad Region (based on Topographic Maps)'. Based on the performed analysis, at the end of the article the authors formulated the key forward-looking trends in the development of the Kaliningrad region's rural settlement taking into account the historical features of its foundation as well as the forecast of the social and economic development of the Russian exclave. Keywords: Kaliningrad region, East Prussia, settlement system, spatial organisation JEL Classifications: R00; R1